Assessment of the efficacy and compliance with Vojea® in women during the pregravid preparation and the early stages of pregnancy - I.N. Kononova; E.N. Kareva; E.V. Stebenyaeva; N.A. Shmakova; I.V. Graban; T.A. Ogurtsova; Yu.E. Dobrokhotova; S.V. Orlova (LCC «Medicine-Inform», 2023)
I.N. Kononova1,2, E.N. Kareva1,3, E.V. Stebenyaeva4, N.A. Shmakova5, I.V. Graban6, T.A. Ogurtsova7, Yu.E. Dobrokhotova1, S.V. Orlova8 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2LLC "Interregional Center for Continuing Professional Education", Moscow, Russian Federation 3I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation 4LLC "SMARTLAB", Yekaterinburg, Russian Federation 5LLC Medical Center "ANGIO LINE PLUS", Yekaterinburg, Russian Federation 6LLC Medical Center "Edelweiss", Aramil, Russian Federation 7Yekaterinburg Clinical Perinatal Center, Yekaterinburg, Russian Federation 8Russian University of Peoples' Friendshiр, Moscow, Russian Federation Aim: to assess the clinical efficacy, safety and tolerability of Vojea® in the prevention of iron-deficiency anemia and folic acid deficiency in women during the preconception (pregravid) period and early stages of pregnancy, as well as to evaluate patient compliance with this product. Patients and Methods: this prospective multi-center observational study was performed in 2022 in four medical centers and women's health clinics of Ekaterinburg. The study included 87 women with latent iron deficiency (mean ferritin level below 15 ng/ml). The first group consisted of 37 women during the pregravid preparation period, and the second group consisted of 50 pregnant patients with up to 12 weeks of pregnancy. Patients received the Vojea® once daily for three months. Clinical and laboratory efficacy (the absence of objective anemia signs and the changes in hemoglobin level, folate and ferritin blood tests over time), as well as tolerability (the rate of adverse events, tolerability of the taken product evaluated using the visual analog scale) was assessed at days 30, 60 and 90 after the beginning of treatment. Results: beginning from the first month of treatment with the studied complex, some positive changes in clinical symptoms and laboratory findings were reported in both groups. By the third month of therapy, the increment of hemoglobin level in the pregravid preparation group was 17 (13.9%) units, the level of ferritin increased by 6.3 times (clinically significant after two months of the product intake), and the level of blood serum folates increased by 4.6 times. In group 2, the increment of hemoglobin level, as pregnancy was progressing, in three months of the product intake reached 19 units (17%), the level of ferritin increased by 5.9 times (clinically significant after two months of treatment), and the level of blood serum folates increased by 3.9 times. In group 1, adverse events were reported only in 2/37 (5.4%) patients who had dark stool color on the 2nd month of follow-up. In group 2, such adverse events as nausea were reported in 3/50 (6%) patients during the 1st month of product intake. All patients informed that the product was well tolerated which ensured high patient compliance. Conclusion: maintaining iron and folic acid homeostasis by oral intake of the Vojea® complex during three months in the preconception period and early stages of pregnancy is a feasible option based on its high efficacy and good tolerability with the minimal risk of side effects, encouraging high patient compliance. Keywords: ferric pyrophosphate, folic acid, pregravid preparation, pregnancy, active metabolite of folic acid, methyltetrahydrofolate, glucosamine salt, Quatrefolic, micronized microencapsulated ferric iron, Vojea, compliance. For citation: Kononova I.N., Kareva E.N., Stebenyaeva E.V. et al. Assessment of the efficacy and compliance with Vojea® in women during the pregravid preparation and the early stages of pregnancy. Russian Journal of Woman and Child Health. 2023;6(2):95-104 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-95-104.